Tahsin Dan Mutqin: Strategi Peningkatan Kualitas Bacaan Al-Qur’an Di Mdta Kota Lintang Aceh Tamiang - Husna, Nurul; Mudrika, Syarifah (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2024)
The strategy of improving the quality of reading the Qur'an with tahsin is very important in order to achieve the word mutqin, in this MDTA the teacher only prioritizes mutqin for his students without prioritizing tahsin first. The purpose of this study was to determine the main challenges faced in improving the quality of reading the Qur'an in MDTA Kota Lintang, and what Tahsin and Mutqin Strategies can be applied to improve the quality of reading the Qur'an in MDTA Kota Lintang. The research method used in this study is Participatory Action Research (PAR) Research, which is one of the research models that seeks something to connect the research process to the process of social change which is included in it with observation, interviews, and learning (education). The results of the study showed that the main challenge faced by MDTA Kota Lintang was that there were no teachers who were experts in the field of tahsin, so teachers only focused on mutqin not on their tahsin. Then the tahsin and mutqin strategies provided by the students were to create learning about tahsin, as well as provide tahsin guidebooks that were distributed to students and teachers who teach at MDTA Kota Lintang Aceh Tamiang